Ensuring the Family Home: The Responsibilities of Queer Scholarship - Ings, Welby (New Zealand Sociology, 2025)
This article is an updated synthesis of the opening keynote address presented at the inaugural national Rainbow Research symposium Rainbow Studies NOW: Legacies of Community, on 23 November 2023 at Te Herenga Waka | Victoria University of Wellington. It examines the experience of queer silencing as a cultural phenomenon and a condition within and beyond the academy. After considering an example of self-selective silencing within New Zealand’s queer history that caused us to lose our subcultural language, it examines instances of repressing queer research both nationally and internationally. Such silencing has included arson attacks on queer archives and the practice of banning queer literature. The article then considers the design and development of Ia , a research dissemination portal recently launched at Te Wānanga Aronui o Tāmaki Makau Rau | Auckland University of Technology. It argues that such initiatives constitute an act of resistance against queer invisibility. The importance of such projects lies in meeting the requirements of New Zealand’s Education and Training Act 2020 and in countering national and global acts of suppression that continue to target the generation and dissemination of queer research.